The effect of tree windbreaks on the microclimate and crop yields in the Western Cape Region of South Africa - Hamlet, Andrew Gordon (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScFor)--University of Stellenbosch, 2000.